2010
DOI: 10.1074/jbc.m110.140517
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Fusion and Syncytium Formation of Heterologous Cells upon Expression of the FGFRL1 Receptor

Abstract: The fusion of mammalian cells into syncytia is a developmental process that is tightly restricted to a limited subset of cells. Besides gamete and placental trophoblast fusion, only macrophages and myogenic stem cells fuse into multinucleated syncytia. In contrast to viral cell fusion, which is mediated by fusogenic glycoproteins that actively merge membranes, mammalian cell fusion is poorly understood at the molecular level. A variety of mammalian transmembrane proteins, among them many of the immunoglobulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…It was therefore concluded that FGFRL1 exerted a negative effect on cell proliferation. These experiments were later repeated with an inducible system utilizing HEK293-TetOn cells that express FGFRL1 from a construct, which is under the control of the Tet transactivator [38]. In the absence of the inducer doxycycline, these cells proliferated like normal HEK293 cells.…”
Section: Biological Effects Of Fgfrl1mentioning
confidence: 99%
See 3 more Smart Citations
“…It was therefore concluded that FGFRL1 exerted a negative effect on cell proliferation. These experiments were later repeated with an inducible system utilizing HEK293-TetOn cells that express FGFRL1 from a construct, which is under the control of the Tet transactivator [38]. In the absence of the inducer doxycycline, these cells proliferated like normal HEK293 cells.…”
Section: Biological Effects Of Fgfrl1mentioning
confidence: 99%
“…Recently, it has also been observed that FGFRL1 has a peculiar effect on cell-cell fusion [38]. The fusion of mammalian cells into large syncytia is a well controlled process that is restricted to a limited set of cells, including gametes, macrophages, myoblasts, and trophoblasts [39,40].…”
Section: Biological Effects Of Fgfrl1mentioning
confidence: 99%
See 2 more Smart Citations
“…The rarity of fusion, the scarcity of reports and the difficulty of detection could explain why cell fusion remained poorly understood [9]. The fusion of mammalian cells into syncytia is regarded as a developmental process that is tightly restricted to a limited subset of cells [10]. HeLa cells expressing fusion proteins have been used to analyse glycoproteins in virus-induced cell fusion, leading to the conclusion that the expression of the fusion protein F enhances susceptibility to cell fusion [11].…”
Section: Introductionmentioning
confidence: 99%